Composite membrane as well as preparation method and application thereof

By using a composite membrane composed of silk fibroin and baicalin, the problems of chronic skin wound healing and scar formation are solved, and the effects of rapid scar-free healing and shortening of the inflammatory period are achieved.

CN119488626AActive Publication Date: 2025-02-21SOUTHWEST UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411711847.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-21
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The prior art is difficult to effectively promote the healing of chronic skin wounds, especially in shortening the inflammation phase and reducing scar formation.

Method used

The membrane matrix formed by the crosslinking of silk fibroin through stable β-sheets is adopted to uniformly disperse the composite membrane of baicalin. By controlling the mass ratio of silk fibroin to baicalin to 100:3-4, the M2-type pole of macrophages is promoted. , shorten the inflammation period and accelerate wound healing.

Benefits of technology

The superior biocompatibility, good hemostasis and controllable biodegradability of the composite membrane are achieved, which promotes rapid scar-free healing of skin wounds and shortens the inflammation period.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488626A_ABST
    Figure CN119488626A_ABST
Patent Text Reader

Abstract

The composite membrane comprises a membrane matrix formed by stable beta folding mutual crosslinking of fibroin and baicalin uniformly dispersed among fibroin molecular chain segments, the mass ratio of fibroin to baicalin is 100: 3-4, and the preparation method of the composite membrane comprises the following steps: 1) taking silkworm cocoons, dissolving and boiling the silkworm cocoons with a sodium carbonate solution for several times, washing the silkworm cocoons, and drying the silkworm cocoons to 60 DEG C; (2) dissolving with a ternary solution, centrifugally filtering to obtain fibroin clear liquid, and drying to obtain fibroin; (3) preparing a fibroin solution with the concentration of 1-30mg / ml from fibroin, and adjusting the pH value to 7.4; and 4) adding baicalin into the fibroin solution, drying after film formation, and annealing to obtain the composite film. The composite membrane has excellent biocompatibility, hemostasis performance and controllable biodegradability, and can promote M2 type polarization of macrophages, shorten the inflammation period and effectively promote skin wound healing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of materials, and in particular to a composite film and a preparation method and application thereof. Background Art

[0002] The skin is the largest organ in the human body and is a protective barrier for the human body from the external environment. Skin trauma is one of the most common injuries. Skin trauma can be divided into acute wounds (such as mechanical trauma, chemical trauma and surgical trauma, etc.) and chronic wounds (burns, infections, diabetes, etc.). The healing of chronic wounds such as burns, infections and diabetes generally takes three months or longer. The wounds not only heal slowly but also easily form scar tissue. For chronic wounds with serious conditions, they heal slowly. If there is a lack of timely intervention to speed up their healing, as the disease progresses, the extremities may become necrotic, and may even be accompanied by symptoms of severe pain. At this time, amputation, skin grafting and other means may be needed to treat the patient. In this case, the patient not only needs to bear huge medical expenses, but also needs to endure long-term pain and mental stress.

[0003] Wound healing consists of four different stages, namely the coagulation phase, the inflammatory phase, the proliferation phase, and the tissue remodeling phase. Macrophages and fibroblasts play an indispensable role in the skin healing process. M1 macrophages can trigger inflammatory responses and kill pathogens, while M2 macrophages are conducive to the resolution of inflammation and the formation of skin tissue. The balance of macrophage polarization to M1 and M2 types plays an important role in the rapid scarless healing of wounds. One of the main cells in the dermis of the skin is fibroblasts. When the skin is damaged, fibroblasts will be recruited to the skin wound in large numbers and differentiate into myofibroblasts under the stimulation of relevant growth factors and cell factors. Myofibroblasts can secrete a large amount of collagen at the wound and provide strong pulling force to promote the process of tissue fibrosis, thereby accelerating the contraction and healing of the wound. However, the continued presence of myofibroblasts will cause scar formation. The construction of wound repair materials that can regulate the inflammatory response and fibroblast differentiation in the wound healing process is expected to achieve rapid scarless healing of difficult-to-heal wounds. Currently, there are many treatments for skin injuries, including autologous transplantation, allogeneic transplantation, wound dressings, etc., but difficult-to-heal wounds and the formation of scar tissue during wound healing remain clinical difficulties.

[0004] Therefore, how to develop a drug that can promote wound healing, especially shorten the inflammatory period, is one of the directions that technicians in this field hope to break through. Summary of the invention

[0005] One of the purposes of the present invention is to provide a composite membrane with excellent biocompatibility, hemostatic properties and controllable biodegradability in order to address the deficiencies of the prior art, and to promote M2 polarization of macrophages, shorten the inflammatory period, and effectively promote skin wound healing.

[0006] The second object of the present invention is to provide a method for preparing the composite membrane, which has a simple and convenient preparation process and is suitable for industrial large-scale production.

[0007] The technical solution for achieving one of the purposes of the present invention is: a composite membrane, comprising a membrane matrix formed by silk fibroin cross-linked with each other in a stable β-folding manner, and baicalin uniformly dispersed between the silk fibroin molecular segments, wherein the mass ratio of the silk fibroin to baicalin is 100:3-4.

[0008] The thickness of the membrane matrix is ​​0.05-0.2 mm, and the mass per unit area is 2.5-4.0, preferably 3.73 mg / cm 2 , the mass ratio of silk fibroin to baicalin is 100:3-4.

[0009] The technical solution for achieving the second object of the present invention is: any method for preparing the above-mentioned composite film comprises the following steps:

[0010] 1) Take the silkworm cocoons, boil them in sodium carbonate solution several times, wash them, and dry them at 60°C;

[0011] 2) dissolving with a ternary solution, centrifuging and filtering to obtain a silk fibroin clear solution, and drying to obtain silk fibroin;

[0012] 3) Prepare a silk solution with a concentration of 1-30 mg / ml and adjust the pH to 7.4;

[0013] 4) adding baicalin to the silk fibroin solution, drying and annealing after film formation to obtain a composite film.

[0014] Step 1) The concentration of the sodium carbonate solution is 0.5 wt %, the number of boilings is three times, the single boiling time is 25-30 min, and washing is performed with clean water.

[0015] Furthermore, in step 2), the ternary solution is a mixture of calcium chloride, ethanol and water, and the molar ratio of calcium chloride, ethanol and water is 1:2:8.

[0016] Preferably, step 2) is dissolved in a 60°C water bath for 1-2 hours, and after complete dissolution, it is naturally cooled to room temperature and centrifuged at a speed of 8000 rpm for 10 minutes. The filtration is performed using a 400-500 mesh nylon cloth, and the silk is freeze-dried at -20°C for 48 hours to obtain silk.

[0017] Preferably, in step 3), ultrapure water is used to dissolve the freeze-dried silk fibroin to prepare a silk fibroin solution, the concentration of the silk fibroin solution is 14 mg / ml, and 1 M sodium hydroxide-1 M acetic acid is used to adjust the pH.

[0018] Furthermore, in step 4), the baicalin is a baicalin solution, the solvent is a silk fibroin solution with a pH of 7.4, the concentration is 3 wt %, and the mass ratio of baicalin to silkworm cocoons is 3:125-140.

[0019] Furthermore, in step 4), the film is formed by tape casting, and after the film is formed, it is dried at 42° C. for 40-44 hours, and then annealed at a humidity of 70-80% for 4-5 hours.

[0020] The present invention also provides use of any of the above composite films in preparing a chronic skin wound repairing drug.

[0021] Furthermore, the medicine is a dressing.

[0022] The above technical solution has the following beneficial effects:

[0023] 1. The composite membrane of the present invention comprises a membrane matrix of silk fibroin cross-linked with each other by forming a stable β-fold, and baicalin uniformly dispersed between the silk fibroin molecular segments on the membrane matrix, wherein the β-fold is a water-insoluble structure, which makes it difficult for the wound to adhere, and the β-fold is irreversible once formed, that is, the properties of this membrane are very stable and convenient for transportation and storage. Several spaces are formed between the molecular segments of the β-fold, and baicalin is divided into these spaces, which is easy to release and can quickly exert its medicinal effect. By controlling the mass ratio of silk fibroin and baicalin to 100:3-4, the biological safety can be increased as much as possible while ensuring the medicinal effect. If the mass ratio is too high, the medicinal effect is insufficient, and if the mass ratio is too low, the cytotoxicity is large and the safety is low. The silk protein in the composite membrane has excellent biocompatibility, good tensile strength, good hemostatic properties, controllable biodegradability and non-cytotoxicity. Its derivative implants also have good immunogenicity. In addition, the degradation products of silk protein materials are composed of soluble peptides and free amino acids, which are easily metabolized and absorbed by the human body and are excellent repair materials. Baicalin is a flavonoid active substance extracted from the traditional Chinese medicine Scutellaria baicalensis root. It is low in cost, easy to extract, and has anti-inflammatory and anti-infective activities. In addition, Scutellaria baicalensis has the effect of promoting the polarization of giant cells M2 type and can shorten the inflammatory period. However, single silk has low anti-inflammatory properties and slow wound healing. Baicalin has low bioavailability when used alone and is not easy to exert its efficacy. The combination of the two can achieve the effect of efficient utilization and strong healing.

[0024] 2. The preparation method of the composite membrane of the present invention comprises repeatedly boiling the cocoons with a Na2CO3 solution having a concentration of 0.5wt% for several times to facilitate the removal of the sericin from the cocoons and subsequent dissolution. After washing with clean water, the cocoons are dried to 60°C to facilitate subsequent dissolution. By drying, the addition of water to destroy the subsequent ternary solution system is prevented.

[0025] 3. The ternary solution configured in the present invention facilitates the subsequent reshaping and generation of the membrane shape by destroying the β-folding of the cocoon. After the membrane is formed, it is annealed for 4-5 hours under a humidity of 70-80%. This environment is conducive to the formation of the β-folding of silk fibroin, and finally a composite membrane with the structure of the present invention is obtained.

[0026] The following is a further description in conjunction with specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The infrared spectrum and peak fitting diagram of the composite film prepared in Example 1;

[0028] Figure 2 is the X-ray diffraction spectrum of the composite film prepared in Example 2;

[0029] Figure 3 The light transmittance test graph of the composite film prepared in Example 2 and the blank film of the control example;

[0030] Figure 4 This is a photo of the composite membrane of Example 2. DETAILED DESCRIPTION

[0031] In the present invention, the silkworm cocoons used are from the National Key Laboratory of Efficient Breeding and Utilization of Resource Insects, baicalin with a purity of 90% is from Aladdin Reagent (Shanghai) Co., Ltd., anhydrous calcium chloride is from Jieshikai with a purity of 99.99%, anhydrous ethanol is from Chengdu Jinshan Chemical Reagent Co., Ltd. with a batch number of 20240806, and ultrapure water is prepared by an instrument (sartorius).

[0032] Prepare a ternary solution of CaCl2 (111 g): CH3CH2OH (92.14 mL): H2O (144 mL) = 1:2:8 (molar ratio).

[0033] Example 1

[0034] 1) Take 10g of silk cocoons, repeatedly boil them with 0.5wt% Na2CO3 solution for 3 times, with each boiling time of 25min, so as to remove the sericin from the cocoons, wash with clean water, and dry them at 60°C for subsequent dissolution;

[0035] 2) Dissolve in 300 ml of ternary solution;

[0036] 3) Centrifuge at 8000 rpm for 10 min, take out the supernatant with a 1000 ul pipette, filter the supernatant with a 400-500 mesh nylon cloth, dialyze the supernatant with an 8000-14000 dialysis bag for 3 days, and then freeze-dry in a freeze dryer for 48 hours (sample temperature -20°C) to obtain freeze-dried silk fibroin;

[0037] 4) Take 70 mg of freeze-dried silk fibroin, add 5 ml of ultrapure water, and prepare 5 ml of 14 mg / ml silk fibroin solution;

[0038] 5) According to the different pH values ​​of the pure water used, the pH of the silk solution was adjusted to 7.4 using 1MNaOH-1MCH3COOH;

[0039] 6) taking 152.1 mg of baicalin solution, adding it to the silk fibroin solution, using a vortex instrument to mix well to obtain a mixed solution, wherein the concentration of the baicalin solution is 3 wt %;

[0040] 7) Take 10 ml of the mixed solution and cast it into a film in a 9 cm polyethylene culture dish without bubbles;

[0041] 8) Dry in an oven at 42°C for 39-42h;

[0042] 9) Turn off the oven, place a beaker containing 100-120 ml of distilled water into the oven, and anneal for 4-5 hours;

[0043] 10) Take out the culture dish and demould it with tweezers to obtain the composite film. Its infrared spectrum and peak fitting are as follows: Figure 1 As shown. Figure 1 It can be seen that the addition of baicalin will not affect the stability of the material. Its beta folding content is as high as 49.3%, and its mechanical properties are excellent. It is a very stable material and is easy to transport.

[0044] Example 2

[0045] 1) Take 15g of silk cocoons, repeatedly boil them with 0.5wt% Na2CO3 solution for 3 times to remove the sericin from the cocoons, wash them with ultrapure water, boil them again with ultrapure water, and dry them to 60°C to facilitate subsequent dissolution;

[0046] 2) Dissolve in 300 ml of ternary solution;

[0047] 3) Centrifuge at 8000 rpm for 10 min, take out the supernatant with a 1000 ul pipette, filter the supernatant with a 400-500 mesh nylon cloth, dialyze the supernatant with an 8000-14000 dialysis bag for 3 days, and then freeze-dry in a freeze dryer for 48 hours (sample temperature -20°C) to obtain freeze-dried silk fibroin;

[0048] 4) Take 140 mg of freeze-dried silk fibroin, add 10 ml of ultrapure water, and prepare 10 ml of 14 mg / ml silk fibroin solution;

[0049] 5) According to the different pH values ​​of the pure water used, the pH of the silk solution was adjusted to 7.4 using 1MNaOH-1MCH3COOH;

[0050] 6) taking 304.2 mg of baicalin solution, adding it to the silk fibroin solution, and mixing it using a vortex instrument to obtain a mixed solution, wherein the concentration of the baicalin solution is 3 wt %;

[0051] 7) Take 10 ml of the mixed solution and cast it into a film in a 9 cm polyethylene culture dish without bubbles;

[0052] 8) Dry in an oven at 42°C for 44-48 hours;

[0053] 9) Turn off the oven, place a beaker containing 150-200 ml of distilled water into the oven, and anneal for 4-5 hours;

[0054] 10) Take out the culture dish and demould it with tweezers to obtain the composite film, whose X-ray diffraction spectrum is as follows: Figure 2 As shown. Figure 2 It can be seen that baicalin may remain in a crystalline state after being loaded in the pure silk fibroin membrane, indicating that baicalin can stably exist in the silk fibroin membrane and exert its medicinal effect.

[0055] Comparative Example 1

[0056] The same as Example 2, except that step 6) is omitted to prepare a pure silk fibroin membrane.

[0057] Comparative Example 2

[0058] The same as Example 2, except that step 9) is omitted, and the prepared membrane material directly dissolves in water, which cannot be verified by animal experiments.

[0059] Comparative Example 3

[0060] The same as Example 1, except that the beaker containing distilled water is not placed in step 9). The obtained membrane material dissolves in water, and the dissolution rate is slower than that of Control Example 2.

[0061] Example 4

[0062] The transmittance of the composite film prepared in Example 2 and the blank film of Control Example 1 was tested. The results are as follows: Figure 3 As shown, from Figure 3 It can be seen that the baicalin-loaded silk fibroin film has a good light transmittance, which can be as high as about 85%. Figure 4 As shown, the school emblem can be clearly seen through the baicalin-loaded silk fibroin film, and good light transmittance is helpful for detecting the recovery of the wound.

[0063] Example 5

[0064] SD rats were divided into three groups, the first group was a blank group, repeated three times, the second group was a test group, using the composite film prepared in Example 2 as a dressing, repeated three times, and the third group used control example 1. The specific operation is as follows:

[0065] ① Male Kunming rats (14 weeks old) from Enswell Biotech were anesthetized with isoflurane (2.5%) for 10 min (there is a slight error depending on the weight of the rats);

[0066] ②Disinfect the operating table and surgical instruments by spraying 75% alcohol;

[0067] ③ Cover the operating table with a disposable sterile surgical sheet

[0068] ④Fix the rat on the operating table, shave the back hair with a blade, wipe the back skin with warm water, and finally disinfect with 75% alcohol;

[0069] ⑤ Use a 10 mm diameter sterile punch to mark the position on the back, lift the skin with sterile tweezers, and cut the skin along the mark with sterile ophthalmic scissors to create a circular full-thickness skin defect;

[0070] ⑥ For the blank group, 3M patch was added, for the test group, baicalin-loaded silk fibroin membrane was added and fixed with 3M patch, for the control group, pure silk fibroin membrane was used and fixed with 3M patch, and the 3M patch and corresponding drug film were replaced every day from 0 to 3 days after the wound;

[0071] ⑦ Record the wound repair status on the back of rats on days 0, 1, 2, 3, 5, 7, and 11;

[0072] ⑧ During this period, rats were raised according to conventional feeding methods.

[0073] The wound healing status is shown in the following table:

[0074]

[0075] As can be seen from the table, the repair rate of the baicalin-loaded silk fibroin membrane was 4.71% higher than that of the control group. This shows that the baicalin-loaded silk fibroin membrane plays a role in ordinary wounds and enhances the repair ability, while the pure silk fibroin membrane causes slow wound recovery due to air circulation obstruction.

Claims

1. A composite film, characterized in that The invention comprises a membrane matrix formed by silk fibroin cross-linked with each other in a stable beta-folding manner, and baicalin uniformly dispersed between the silk fibroin molecular chain segments, wherein the mass ratio of the silk fibroin to the baicalin is 100:3-4.

2. The composite membrane according to claim 1, characterized in that The thickness of the membrane matrix is ​​0.05-0.2 mm, and the mass per unit area is 2.5-4.0 mg / cm 2 , preferably 3.73 mg / cm 2 , the mass ratio of silk fibroin to baicalin is 100:3-4.

3. The method for preparing the composite membrane according to claim 1 or 2, characterized in that: The following steps are involved: 1) Take the silkworm cocoons, boil them in sodium carbonate solution several times, wash them, and dry them at 60°C; 2) dissolving with a ternary solution, centrifuging and filtering to obtain a silk fibroin clear solution, and drying to obtain silk fibroin; 3) Prepare a silk solution with a concentration of 1-30 mg / ml and adjust the pH to 7.4; 4) adding baicalin to the silk fibroin solution, drying and annealing after film formation to obtain a composite film.

4. The preparation method according to claim 3, characterized in that: Step 1) the concentration of the sodium carbonate solution is 0.5wt%, the number of dissolutions is three times, the single dissolution time is 25-30min, and clean water is used for washing. Step 2) the ternary solution is a mixture of calcium chloride, ethanol and water, and the molar ratio of calcium chloride, ethanol and water is 1:2:

8.

5. The preparation method according to claim 3, characterized in that: Step 2) dissolving in a 60°C water bath for 1-2 hours, cooling naturally to room temperature and centrifuging after complete dissolution, the centrifugal speed is 8000 rpm, the centrifugal time is 10 minutes, filtering is performed using 400-500 mesh nylon cloth, and freeze-drying is performed at -20°C for 48 hours to obtain silk fibroin.

6. The preparation method according to claim 3, characterized in that: Step 3) Dissolve the freeze-dried silk fibroin in ultrapure water to prepare a silk fibroin solution, the concentration of the silk fibroin solution is 14 mg / ml, and the pH is adjusted using 1 M sodium hydroxide-1 M acetic acid.

7. The preparation method according to claim 3, characterized in that: Step 4) Baicalin is a baicalin solution, the solvent is a silk fibroin solution with a pH of 7.4, the concentration is 3wt%, and the mass ratio of baicalin to silkworm cocoon is 3:125-140.

8. The preparation method according to claim 3, characterized in that: Step 4) forming the film by tape casting, drying the film at 42° C. for 40-44 hours, and then annealing the film at a humidity of 70-80% for 4-5 hours.

9. Use of the composite film according to claim 1 or 2 in preparing a drug for repairing chronic skin wounds.

10. The use according to claim 9, characterized in that: The medicine is a dressing.

Citation Information

Patent Citations

  • Collagen polypeptide burn repair film and preparation method thereof

    CN103893822A

  • Preparation method of silk fiber fibroin hemostasis material

    CN106317446A

  • Preparation method of curcumin-containing medical dressing based on silk fibroin

    CN110448715A

  • A macrophage conditioned medium for promoting wound healing, dressing, preparation method and application thereof

    TWI640631B

  • Freeze-dried powder of high molecular weight silk fibroin, preparation method therefor and use thereof

    US20170107264A1